2007
DOI: 10.1111/j.1442-2018.2007.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a diabetes self‐management program on glycemic control, coronary heart disease risk, and quality of life among Thai patients with type 2 diabetes

Abstract: Uncontrolled diabetes is a major health problem in Thailand. The objective of this study was to determine the effects of a diabetes self-management program on glycemic control, coronary heart disease (CHD) risk, and quality of life in 147 diabetic patients (aged 56.8 +/- 10.2 years). Type 2 diabetic patients who met the research criteria were randomized into two groups for a period of 6 months: the experimental group received the diabetes self-management program and the control group received the usual nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(162 citation statements)
references
References 25 publications
(18 reference statements)
6
153
0
3
Order By: Relevance
“…The present study promoted goal setting for glycemic control, blood pressure control, weight control and encouraged patients to change their behaviors through education and reinforcement using a home-visiting approach. Also, as in our study, the other study reports supported the effects on glycemic control and behavior as result of self-management training [18,24,25]. But we have some diffi culties.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The present study promoted goal setting for glycemic control, blood pressure control, weight control and encouraged patients to change their behaviors through education and reinforcement using a home-visiting approach. Also, as in our study, the other study reports supported the effects on glycemic control and behavior as result of self-management training [18,24,25]. But we have some diffi culties.…”
Section: Discussionsupporting
confidence: 63%
“…Schwedes et al, who conducted meal-related, structured self-monitoring of blood glucose levels to improve diabetic control, were able to achieve decreased coronary heart risk in their patients [30]. The study of Wattana et al, noted that at the end of a diabetes self-management programme, there was a reduction in the patients' coronary heart risk in favor of the experimental group [25].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 We therefore focused exclusively on the impact of preventing such complications and their associated expenditure. We first estimated how much it would cost in terms of GDP per capita to avoid one case of diabetes-related complications for a year, using data from Venkat Narayan et al, 30 Wattana et al, 32 and the World Health Organization. 33 We then estimated how many cases of complications one would have to prevent in order to prevent one case of complications-related catastrophic expenditure, using Chatterjee et al 9 Putting these together yields the reported estimate of the GDP per capita required to prevent one case of catastrophic expenditure via preventing complications from diabetes.…”
Section: Financial Risk Protectionmentioning
confidence: 99%
“…In the clinical practice, the enhancement of self-efficacy has been shown to improve symptoms of chronic disease, such as diabetes, indicating that self-efficacy represents an antecedent to behaviour modification (Smarr et al, 1997;Wattana et al, 2007). For example, Smarr et al (1997) examined the relationship between induced changes in selfefficacy following a stress management programme and outcome measures of depression, pain, health status, and disease status in rheumatoid arthritis patients, and found a significant association between self-efficacy modification and the clinically relevant outcome measures.…”
Section: Self-efficacy In the Clinical Practicementioning
confidence: 99%